Pemanfaatan Media Sosial Sebagai Media Pembelajaran dalam Meningkatkan Wawasan Keagamaan Siswa - Rafi Aiman Razani; Mokh Iman Firmansyah; Ganjar Eka Subakti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The abundance of content circulating on social media poses a significant challenge for the world of education, as much of it can lead to a decline in students' religious awareness. This article aims to determine the effectiveness of social media use in education, specifically in increasing students' religious insight and religious awareness when using the internet. The research method used was qualitative with a descriptive approach through observation, interviews, and documentation of Islamic Religious Education teachers and students at SMAN 1 Dayeuhkolot. The results showed that the use of social media such as WhatsApp, Instagram, and YouTube in giving Islamic Religious Education assignments was able to increase student participation, interest in learning, and understanding of religious values. This study concluded that social media can be an effective tool in supporting Islamic Religious Education learning and increasing religious awareness if used wisely and in a targeted manner.